Pengaruh Bauran Pemasaran (Produk, Harga, Tempat, Promosi) terhadap Volume Penjualan di Cafe Shop Senyala Space Kota Jambi - Ahmad Syahrizal; Usdeldi Usdeldi; Firman Syah Noor (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2026)
This study aims to examine the influence of the marketing mix on the sales volume at Senyala Space coffee shop, focusing on four independent variables: product, price, place, and promotion. The research method used is quantitative with a descriptive approach. The population of the study consists of Senyala Space customers from 2020 to 2024, and the sample was selected using nonprobability sampling and Slovin’s technique to determine a representative sample size. Data was collected through surveys and interviews with customers who visited Senyala Space during the specified period. Data analysis was conducted using several statistical tests, including validity testing, reliability testing, normality testing, linearity testing, multicollinearity testing, heteroscedasticity testing, and multiple linear regression analysis. Additionally, the coefficient of determination (R²), partial test (t-test), and simultaneous test (F-test) were used to examine the effect of independent variables on the dependent variable. All analyses were performed using IBM SPSS Statistics 23. The results show that the marketing mix significantly affects the sales volume at Senyala Space. Of the four marketing mix variables analyzed, price was found to have a significant negative effect on sales volume, indicating that an increase in price tends to decrease sales volume. On the other hand, the other three variables—product, place, and promotion—have a significant positive effect on sales volume. This suggests that improvements in product quality, strategic location selection, and effective promotions can increase sales at Senyala Space. These findings provide recommendations for Senyala Space’s management to enhance their marketing strategies by considering the factors influencing customer purchasing decisions, in order to boost sales volume in the future.